2017
DOI: 10.1002/pi.5398
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble cellulose oligomer production by chemical and enzymatic synthesis: a mini-review

Abstract: This mini‐review focuses on the production of water‐soluble cellulose oligomers. They are easier to handle than cellulose while still having some very interesting cellulose features. Their production is not trivial and they are thus seldom commercially available or are available at high prices and only in small quantities (100 mg or less). The goal of this mini‐review is to describe various routes to obtain these cellulose oligomers. Several examples of chemical or enzymatic synthesis and enzymatic or acidic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 130 publications
(148 reference statements)
1
23
0
Order By: Relevance
“…Animal studies have shown that adding cello‐oligosaccharides to the feed of calves causes fewer incidences of gastrointestinal infections and reduces the use of antibiotics . Cello‐oligosaccharides also have the potential to act as a non‐digestible prebiotic that can reduce the risk of lifestyle diseases in humans by promoting the growth of beneficial bacteria and inhibiting pathogenic bacterial species in the gastrointestinal tract . Thus, cello‐oligosaccharides can provide multiple benefits to the agricultural and healthcare industries.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that adding cello‐oligosaccharides to the feed of calves causes fewer incidences of gastrointestinal infections and reduces the use of antibiotics . Cello‐oligosaccharides also have the potential to act as a non‐digestible prebiotic that can reduce the risk of lifestyle diseases in humans by promoting the growth of beneficial bacteria and inhibiting pathogenic bacterial species in the gastrointestinal tract . Thus, cello‐oligosaccharides can provide multiple benefits to the agricultural and healthcare industries.…”
Section: Figurementioning
confidence: 99%
“…Cellobiose, containing two glucose units, is the only commercially available cello‐oligosaccharide. Higher cello‐oligosaccharides are produced in small amounts and are up to 500 times more expensive . Commercial application of cello‐oligosaccharides is not feasible until a cost‐effective process is developed for their synthesis.…”
Section: Figurementioning
confidence: 99%
“…To further develop their promising applications, the soluble cellodextrins must be produced efficiently at large scale. Reported routes for their preparation are based upon depolymerization of cellulose or bottom‐up synthesis . Chemical and enzymatic methods are known for both types of route .…”
Section: Introductionmentioning
confidence: 99%
“…Reported routes for their preparation are based upon depolymerization of cellulose or bottom‐up synthesis . Chemical and enzymatic methods are known for both types of route . Control of the product DP is essential and remains a challenge .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation